The role of research in Antarctic diplomacy: A scientometric analysis of the Treaty System’s impact - Zherebchuk, Sofiia; Kudas, Dmytro; Kuz, Sergiy (Ukrainian Antarctic Journal, 2025)
This study delves into the intricate relationship between scientific research and diplomacy within the framework of the Antarctic Treaty System (ATS), employing a comprehensive scientometric analysis to explore its multifaceted impact. The ATS has played a pivotal role in fostering collaboration among nations. By analysing global publication trends, citation patterns, and co-authorship networks, this research examines how scientific output not only reflects but also drives international cooperation and policy development in polar regions. The primary objective of this study is to evaluate the role of research output in supporting the principles of the ATS, with a focus on promoting peace, science, and environmental protection in Antarctica. Specifically, it aims to іnvestigate the contribution of scientific research to international collaboration under the ATS; іdentify global trends and emerging priorities in Antarctic research; assess the impact of interdisciplinary studies in advancing ATS objectives, including climate change mitigation and ecosystem protection. This research adopts a scientometric approach to analyse the global corpus of scientific publications related to Antarctic research. The analysis revealed that the volume of Antarctic related scientific publications has grown significantly over the last two decades, with a notable increase in interdisciplinary studies addressing climate change, biodiversity, and polar ecosystem dynamics. Co-authorship networks highlighted a robust level of international collaboration, underscoring the treaty’s success in fostering scientific partnerships. Moreover, open data initiatives, driven by the ATS, were found to play a crucial role in advancing research efficiency and promoting transparency. The study also found that scientific output often influences policy discussions, particularly on climate change mitigation, the designation of marine protected areas, and sustainable resource management in Antarctica. The integration of research into ATS decision-making processes strengthens its effectiveness as a governance system while showcasing the role of science diplomacy in addressing global challenges.